A Comparative Study between Transcutaneous Bilirubinometry and Total Serum Bilirubin Measurement in Jaundiced Newborns - Alsaeedi, Bahjat Abdulridha; Mohammed, Razan Ali; Al-Rubaye, Waad Edan Louis (AL-Kindy College Medical Journal, 2022)
Background: Drawing blood to measure total serum bilirubin is painful & time consuming. Transcutaneous bilirubinometer working by multiwavelength spectral reflectance from the skin surface on forehead or upper sternum is a quick & painless technique. Objectives: to compare the effectiveness of transcutaneous (over the upper sternum and forehead) and serum bilirubin measurement of neonate with jaundice.Subjects and Methods: This is a cross sectional prospective study. It enrolled 175 jaundiced neonates & excluded those exposed to phototherapy. It was conducted at Child Central Teaching Hospital in Baghdad, Iraq from the 1st of August to the 30th of October 2018. Transcutaneous bilirubin measurement on forehead and upper sternum was done by JM 103 Minolta Air shields bilirubinometer. Total serum bilirubin was measured by APEL BR 501 BILIRUBIN METER. Data entered & analyzed using SPSS 20 computer software. Means, frequencies, cutoff values, sensitivity & specificity were calculated. Results: The mean age, gestational age & birth weight were (6.3±4.3 days), (36.9±2.1 weeks) and (2.7±0.6 Kg) respectively. Mean total serum bilirubin, transcutaneous chest & forehead bilirubin levels were 12.6±4.2 mg/dl, 11.8±3.8 mg/dl & 11.2±3.9 mg/dl respectively. Mean total serum bilirubin was significantly higher than transcutaneous chest and forehead bilirubin. Cutoff values of transcutaneous chest & forehead bilirubin levels were [(9 mg/dl) with sensitivity (95.4%) & specificity (86.4%)] and [(8.2 mg/dl) with sensitivity (94.7%) & specificity (86.4%)] respectively.Conclusions: Transcutaneous bilirubin measurements on chest and forehead have an acceptable validity in predicting hyperbilirubinemia with less accuracy on forehead.